Efficacy of hybrid endoscopic submucosal dissection (ESD) as a rescue treatment in difficult colorectal ESD cases. (20th April 2017) - Okamoto, Koichi; Muguruma, Naoki; Kagemoto, Kaizo; Mitsui, Yasuhiro; Fujimoto, Daisaku; Kitamura, Shinji; Kimura, Tetsuo; Sogabe, Masahiro; Miyamoto, Hiroshi; Takayama, Tetsuji
Abstract : Background and Aim: Endoscopic submucosal dissection (ESD), which provides a higher en bloc resection rate than conventional endoscopic mucosal resection (EMR), is considered to be a useful treatment option for large colorectal tumors. However, colorectal ESD is not widely used because of its technical difficulty, risk of complications and time required. To overcome these drawbacks, a simpler modified technique, ESD with snaring (hybrid ESD), has been developed. The aim of the present study was to retrospectively compare the safety and efficacy of hybrid ESD and conventional ESD for colorectal tumors. Methods: Between September 2008 and June 2016, ESD was carried out on 137 lesions and hybrid ESD on 27 lesions. All hybrid ESD cases were carried out as a rescue treatment in difficult ESD cases. We retrospectively investigated procedure time, and the rates of en bloc resection, perforation, bleeding, and local recurrence. Results: In the hybrid ESD group, procedure time was shorter compared with the ESD group (108 ± 59.5 min vs 122 ± 72.2 min), but the en bloc resection rate was lower (66.7% vs 94.2%). However, there were no significant differences in procedure time, or in rates of en bloc resection, perforation and bleeding between the two groups. Local recurrence did not develop in any of our cases. Conclusions: Hybrid ESD as a rescue treatment in difficult ESD cases may be less effective for en bloc resection of large colorectal tumors. Indication for hybrid ESD may be limited to scheduled treatment from the outset and emergency cases with patients who present unstable vital signs during ESD.